The astronomical lantern slide set and the Eidouranion in Australia. Issue 1 (2nd January 2019) - Bush, Martin
ABSTRACT: Astronomical lantern slide sets were amongst the first to be commercially produced, and also amongst the most long-lasting. The visual techniques of lanternism were shaped by the earlier practice of stage astronomy, involving devices like the Eidouranion and the Dioastrodoxon. In this article I describe the extent of this tradition in colonial Australia and argue that an examination of less central examples is revealing of its full influence. Evidence for a number of transparent orreries in Australia is presented, including that of John Cox in Sydney, and Phineas Moss in Tasmania. Other references to the devices of stage astronomy, such as by Laurence Hynes Halloran, are also described.